Assessment of pain management adequacy among hospitalized pediatric patients: institutional-based cross-sectional study - Kasahun, Asmamaw Emagn; Sendekie, Ashenafi Kibret; Abebe, Rahel Belete (Frontiers in Pediatrics, 2023)
Background: As the evidence showed, despite the magnitude of the effects that pain can have on a child, it is often inadequately assessed and treated. However, whether pain is adequately treated or not, evidence is lacking in the study setting. Objectives: This study assessed pain management adequacy among hospitalized pediatric patients at the University of Gondar Comprehensive Specialized Hospital, Ethiopia. Methods: An institution-based cross-sectional study was conducted among pediatric patients admitted to the University of Gondar Comprehensive and Specialized Hospital between June and August 2021. Eligible patients were enrolled in the study using consecutive sampling techniques. Data were collected using a structured interview-based questionnaire and a review of the patient’s medical records that were prepared after reviewing earlier studies. Pain management adequacy was determined using the pain management index (PMI) score. Statistical Software for Social Sciences (SPSS) version 22 was used for data entry and analysis. Descriptive statistics such as frequencies, percentages, and means with standard deviation were used to describe the respective variables. Logistic regression was used to assess predictor variables of pain management adequacy. A p-value < 0.05 at a 95% CI was considered statistically significant. Results: Of the 422 participants enrolled in the study, most (58.1%) were males, with a mean age of 3.9±0.8 years. Pain medication was prescribed to 62.8% (95% CI: 57.3–68.2) of the participants. About 63.3% (95% CI: 58.8–68%) received inadequate analgesics. The type of painkillers administered also did not match the severity of the pain. Pediatric patients less than one month and between one month and one year (AOR = 2.891, 95% CI: 1.274–12.899 and AOR = 2.657, 95% CI: 1.350–5.175), respectively, and patients with severe and moderate levels of pain (AOR = 3.448, 95% CI: 1.902–6.251 and AOR = 5.345, 95% CI: 1.956–9.828), respectively, were found to have inadequate pain medication compared with their counterparts. Conclusion: This study revealed that pain was hardly managed based on its severity. Overall, two-thirds of pediatric patients received inadequate pain medication. This indicates majority of patients experienced pain did not manage appropriately.